In vitro multiplication of 'Flordaguard' rootstock: cytokinin source and concentration effects, explants orientation and period of permanence in the culture medium - Radmann,Elizete Beatriz (2011)
This work aimed at studying the effects of different sources and cytokinin concentrations, as well as explants orientation and time of their permanence in shoots induction medium to obtain high multiplication rate. Four experiments were carried out to evaluate the sprout percentage mean, shoots number per explant, elongated shoots percentage and shoots length. The treatments with 2iP and zeatin did not promote in vitro plant multiplication. When different BAP concentrations were tested, an increase in sprout percentage was obtained using BAP concentration up to 3.66 mg L-1 (80%), and for shoots number per explant a linear behavior was observed, showing a mean of four shoots per explant with 4.0 mg L-1 BAP. For the 'Flordaguard' rootstocks, the explants orientation did not alter the potential in vitro multiplication and the shoots growth. However, the explants permanence in the shoots induction medium for 40 days provided the best results for shoots growth.